Study habits among Nigerian secondary school students with brain fag syndrome - Olufemi Morakinyo; Bolanle Adeyemi Ola (Mental Illness)
Brain Fag Syndrome (BFS) is a psychiatric disorder associated with study affecting two to four out of every ten African students. One of the consequences of this illness is early foreclosure of education in affected students. Etiological factors such as nervous predisposition, motivation for achievement, and psycho-stimulant use have been found associated with it. However, the contributions of study habits to the pathogenesis of this study-related illness deserve more attention than has been given. We carried out this cross-sectional study to ascertain the types of study habits associated with BFS among a sample of senior secondary school students in Ile-Ife, Nigeria. Five hundred students from six schools in Ile-Ife were selected using a stratified random sampling technique. The selected students completed the Socio-demographic Data Schedule, the Brain Fag Syndrome Scale, and Bakare’s Study Habit Inventory. The prevalence of BFS was 40.2% (201). There were no significant socio-demographic variables identifying BFS students apart from those without BFS. The significant measures of study habits that predicted BFS were homework and assignments, examinations, and written work. Those with BFS had 3.58 times the odds to perform poorly on homework and assignments, 3.27 times the odds to perform poorly on examinations, and 1.01 times the odds to perform poorly on written work compared to those without BFS. We concluded that the results of this study suggest that homework and assignments, examinations, and written work were significant study habit variables associated with BFS.